Democratic governance in a selection of cooperatives in Tshwane Metropolitan area - Kgosinyane, Pogisho Godfrey (My University, 2019)
Cooperative principles and values are hailed as the guiding light that ensures that cooperatives serve their members and improve their economic conditions rather than maximise profit. This study explored the views of cooperative members on how they understand the meaning of the cooperative principle of democratic member control. The study also considered whether cooperatives adhere to cooperative principles and what the role of the state is within the cooperative businesses in the study. The cooperative identity as defined by the International Cooperative Alliance (ICA) was examined as well as the economic pressures and challenges that threaten the distinct cooperative character, especially the democratic member control principle. Purposive sampling was used to gather data from participants using semi-structured interviews. The study revealed that members of cooperatives are unaware of the cooperative principles and values. While members of the cooperatives are aware that a cooperative should be run democratically and collectively by its members, the study revealed that a minimalist form of democracy was practiced in the day-to-day life of the cooperatives.
A research report submitted in 50% completion of the degree of Master of Management in the field of Public and Development Management to the Faculty of Commerce, Law and Management, Wits School of Governance, at the University of the Witwatersrand, 2019
Keywords: Cooperative; Cooperative principles; Democracy; Cooperative values; UCTD